The Challenges of Implementing the Emirates Standardized Test as a Proficiency Test in the UAE: An Exploratory Study - Khalil, Abdelhamid A. (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)